Some Metallurgical Aspects of the Blade Fatigue Problem in Aircraft Gas Turbines - K. B. Young (Canadian Institute of Mining, Metallurgy and Petroleum, 1958)
Possibly the most complex fatigue problem associated with the development of the axial-flow 'gas turbine is discussed in its broader aspects from the metallurgical viewpoint. Reference is made to nodal patterns, interference diagrams, etc. The use of such data in analysis of a turbine :blade failure is illustrated. Special attention is given to the influence of some metallurgical variables affecting fatigue strength and, in particular, heat treatment is shown to have a pronounced effect on .the relative fatigue and creep strength properties of a nickel-chromium-cobalt base alloy suitable for turbine blade applications.